An evaluation of the ‘Lego® Therapy’ intervention used to support children with social communication difficulties in their mainstream classroom - Boyne, Sarah E. J. (2014)
This study presents an evaluation of the Lego® Therapy intervention (LeGoff, 2004) for six children, aged six to ten, with varying social communication difficulties. Lego® Therapy is a small-group, child-led and peer-based social development programme. Relevant theory and existing literature is explored firstly, before a systematic review of social communication intervention evaluations is presented. This is followed by a review of current Lego® Therapy studies, highlighting the limited evidence base that has been developed thus far. The present study’s aims of extending and applying more reliable and valid research designs to evaluate the intervention are then presented.